Defects in Germinal Center Selection in SLE - Woods, Megan; Zou, Yong-Rui; Davidson, Anne (Frontiers in Immunology, 2015)
Germinal centers (GCs) are the primary site at which clonal expansion and affinity maturation of B cells occurs. B cells encounter antigen and receive T cell help in the GC light zone (LZ) and then migrate to the dark zone where they proliferate and undergo somatic mutation before cycling back to the LZ for further rounds of selection. Tolerance to autoantigens is frequently lost de novo as GC B cells undergo class switching and somatic mutation. This loss of tolerance is regulated by a variety of mechanisms including cell death, failure to compete for T cell help and failure to differentiate into effector cells. Systemic Lupus Erythematosus (SLE) is characterized by loss of tolerance to nucleic acid antigens. While defects in tolerance occur in the naïve repertoire of SLE patients, pathogenic autoantibodies also arise in the GC as a result of failure to exclude autoreactive B cells from the GC and by somatic mutation from non-autoreactive precursors. Several B cell defects contribute to the loss of GC tolerance in SLE, including polymorphisms of genes that regulate BCR signaling, excess TLR7 signaling, defects in FcRIIB expression or defects of B cell apoptosis. Extrinsic soluble factors such as Type1 IFN or an imbalance between the number of TFH cells and regulatory T cells in the GC can also alter B cell negative selection. Finally, defects in macrophage clearance of apoptotic debris within the GC result in BCR mediated internalization of nucleic acid containing material and stimulation of autoantibody production by endosomal TLR driven mechanisms.